Women’s educational attainment, full-time farming, and household dietary quality in rural China - Li, Rong; Ye, Linxiang; Han, Jingwei (Frontiers in Nutrition, 2025)
Diet serves as the primary source of nutrition, and dietary quality determines individuals’ nutritional status. Poor dietary quality may result in malnutrition such as undernutrition and overnutrition. This study examines the association between women’s educational attainment and rural household dietary quality and the heterogeneity in this association when accounting for the employment status of male and female household heads. We use dietary intake data for 2,069 households from the first round of China Rural Revitalization Survey (2020) and conceptualize dietary quality using the Diet Balance Index (DBI). Multiple linear regression indicates that a one-standard-deviation increase in women’s years of education reduces dietary imbalance by 3.65%, overconsumption by 6.51%, and underconsumption by 2.09%. Specifically, higher education attainment is associated with less inadequate consumption of milk and fish and more balanced meat intake in rural households. Heterogeneity analysis shows that the positive effect of women’s education on dietary quality is stronger when women engage in on-farm employment, while it is more pronounced in households where men are employed in off-farm work. The findings of this research provide theoretical support for improving the nutritional status of rural residents in China and other developing regions by allocating more educational resources and enhancing access to education for rural women.